Peningkatan Kemandirian Santri Lintang Songo Bantul dan Upaya Pelestarian Warisan Islam Nusantara Melalui Produksi Kaos Arab Pegon - Aini, Nur; Sofiana, Ratna; Saifullah, Muhammad (Universitas Nurul Jadid, 2024)
The Lintang Songo Bantul Islamic Boarding School is one of the Islamic boarding school institutions that emphasizes aspects of entrepreneurial independence for its students. This community service is carried out to increase the independence aspect of the students through the production of t-shirts with Arabic Pegon inscriptions. This activity was chosen because previously the students had been equipped with expertise in the field of convection, but there were no specific specifications that would be developed by the students. The production of Arab Pegon t-shirts is an effective breakthrough because 1. The students have been equipped with expertise in the field of convection; 2. T-shirts are a convection product that can be accepted by all ages and groups; 3. Pegon Arabic script is a characteristic of Islamic boarding school products as well as an effort to maintain the Islamic heritage of the archipelago. The stages of activities carried out in community service are: 1. Workshop on writing Pegon Arabic script; 2. Entrepreneurial motivation and business analysis in the t-shirt sector; 3. Training on Arab Pegon t-shirt design and content; 4. Theory and practice of Arab Pegon t-shirt screen printing. The results of the implementation of the service are: 1. Based on the results of the pre-test and post-test, it shows that there is an increase in the students' ability to write and read the Pegon Arabic script; 2. The students understand the ins and outs of the t-shirt business; 3. Creation of several t-shirt designs and content; Students can independently apply screen printing techniques on t-shirts with special designs bearing the Arabic Pegon script